Continuous Wave of Condensation Improves the Filling of Curved Canals: a Micro-CT Study - Pinto, Jader Camilo (2026)
The aim of this study was to compare the filling capacity in curved root canal using a new continuous wave of condensation technique (Termo Pack II, Easy Dental Equipments, Brazil) or lateral compaction. The percentage of voids in the filling of mesial root canals of mandibular molars was assessed by micro-computed tomography (micro-CT). Mesial root canals (n=24) of mandibular molars with a degree of curvature between 20° and 40° were prepared using rotary system (ProDesign Logic, Easy, Brazil) up to #35, .05 taper. The root canals were filled by using the continuous wave of condensation system or lateral compaction and AH Plus sealer (n=12). Scanning at 9 µm was performed after preparation and after filling by using micro-CT SkyScan 1176. The volumetric percentage of filling material and voids (total length and in each root canal third) were calculated. Data were analyzed using ANOVA/Tukey and Student’s t tests (α=0.05). Before the filling techniques, the root canals volume after preparation was similar (p>0.05). The root canals filled by the continuous wave of condensation technique presented the lowest percentage of voids, and the greatest percentage of filling material in total length and thirds (cervical, middle and apical) (p<0.05). Both techniques were not able of completely filling the root canals. The continuous wave of condensation technique Termo Pack II promoted better root canal filling in curved root canals, when compared with lateral compaction.